Keuangan Publik Ibn Taimiyah dan Permasalahan Pajak Pada Era Kontemporer - Susilo, Adib (Iqtishodia: Jurnal Ekonomi Syariah, 2017)
Good public finance management becomes an important thing to create people???s welfare. In the management of public finances, the country???s largest incomes are tax and customs. The injustice of tax distribution is a major problem facing our goverment. In Islam, the discourse on public finance and taxes has been a long and serious study. The management of public finances and taxes according to Ibn Taimiyyah is an interesting study to be presented in this study, and then relating it to the tax problems faced at this time. This article is a literature research that reveals the management of public finances according to Ibn Taimiyyah . By the content analisys, this reasearch concluded that in the public financial mecanism, Ibn Taimiyyah classified the main country???s income (ghanimah, fai, zakat) and secondary (amwal fadhla, luqatah, usr, etc) of the state as well as for what income is incurred through neat administration (diwan). Meanwhile, the solution offered as a policy for tax fraud is to provide punishment and reward, tax amnesty and reporting taxpayer wealth and finance. Keyword: Public Finance, Tax, Shariah Economic